Explicit port-Hamiltonian formulation of multi-bond graphs for an automated model generation. (October 2020) - Pfeifer, Martin; Caspart, Sven; Hampel, Silja; Muller, Charles; Krebs, Stefan; Hohmann, Sören
Abstract: Port-Hamiltonian system theory is a well-known framework for the control of complex physical systems. The majority of port-Hamiltonian control design methods base on an explicit input-state-output port-Hamiltonian model for the system under consideration. However in the literature, little effort has been made towards a systematic, automatable derivation of such explicit models. In this paper, we present a constructive, formally rigorous method for an explicit port-Hamiltonian formulation of multi-bond graphs. Two conditions, one necessary and one sufficient, for the existence of an explicit port-Hamiltonian formulation of a multi-bond graph are given. We summarise our approach in an algorithm for the automated generation of an explicit port-Hamiltonian model from a given multi-bond graph. An academic example illustrates the results of this paper.